2009
DOI: 10.1007/s11430-009-0076-1
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and geological significance of 17α(H)-diahopanes from different hydrocarbon source rocks of Yanchang Formation in Ordos Basin

Abstract: Based on GC-MS testing data of many saturated hydrocarbon samples, 17α(H)-C 30 diahopanes (C 30 * ) are extensively distributed in the lacustrine hydrocarbon source rocks of the Yanchang Formation in OrdosBasin, but show remarkable differences in relative abundance among various source rocks. Generally, Chang 7 high-quality source rock (oil shale) developed in deep lake anoxic environment shows lower C 30 * content, whereas Chang 6-9 dark mudstone developed in shallow to semi-deep lake, sub-oxidizing environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 10 publications
1
18
0
Order By: Relevance
“…The lake basin subsequently evolved into its final stage, and Chang 1, 2 and 3 sections were mainly deposited in the resulting deltaic environment. Oil shale, black shale and carbonaceous shale are very common in semi-deep and deep-lake conditions in the Chang 7 section, and petroleum resources have been well correlated with the shales in this section, which contains abundant organic matters (Duan et al, 2008;Zhang et al, 2009). The Chang 9 shales also have a very high potential for oil generation (Zhang et al, 2007).…”
Section: Geological Background and Samplesmentioning
confidence: 95%
“…The lake basin subsequently evolved into its final stage, and Chang 1, 2 and 3 sections were mainly deposited in the resulting deltaic environment. Oil shale, black shale and carbonaceous shale are very common in semi-deep and deep-lake conditions in the Chang 7 section, and petroleum resources have been well correlated with the shales in this section, which contains abundant organic matters (Duan et al, 2008;Zhang et al, 2009). The Chang 9 shales also have a very high potential for oil generation (Zhang et al, 2007).…”
Section: Geological Background and Samplesmentioning
confidence: 95%
“…The sequence of the Yanchang Formation is subdivided into 10 informal oil reservoir units named Chang 1 to Chang 10 from top to bottom, based on marker beds, sedimentary cycles and lithological associations (Fig 2; (Guo et al, 2014;Ji et al, 2008;Qiu et al, 2015). Oil shale, black shale and carbonaceous shale in bottom of Chang 7 constitute the best source rocks of Yanchang formation (Duan, 2012;Duan et al, 2008;Zhang et al, 2009). The source rocks are mainly humic-sapropel type and minor sapropel type and the R o values of the source rocks range from 0.66% to 1.07% (Duan et al, 2008;Zhao et al, 1996).…”
Section: Yanchang Formation Stratigraphymentioning
confidence: 99%
“…In the last decades the source rocks from Chang 7 unit, which could be used for oil-source rock correlation and thus facilitate hydrocarbon exploration, have attracted much attention (e.g. (Ma et al, 2005;Xi et al, 2008;Zhang et al, 2009). However, in recent years, debris flows and turbidity sandstones at the top of Chang 7 have been found as oil and gas reservoirs, which are known as tight sandstone reservoirs (Yang et al, 2010).…”
Section: Yanchang Formation Stratigraphymentioning
confidence: 99%
“…Although the precursors of rearranged hopanes are not directly derived from terrestrial higher plants, a genetic connection between them seems apparent. Zhang et al (2009) suggested that high to extremely high C 30 diahopane values are indicative of sub-oxidizing environment of fresh-brackish water and shallow to semideep lake. Previous studies indicate that the Songliao Basin develops a brackish-saline lacustrine environment with a mixed input, whereas coal-measure source rocks develop well in sedimentary environments of the Tarim and Ordos Basins (Zhang and Zhu 1996;Zhang et al 2013;Cheng et al 2014).…”
Section: Geochemical Significances Of Rearranged Hopanesmentioning
confidence: 99%
“…In recent years, rearranged hopanes have received increasing attention as biological markers with applications for geochemical studies of petroleum source rocks and crude oils (Huang et al 2003;Li et al 2009;Zhang et al 2009;Cheng et al 2014). However, systematic identification of the four rearranged hopane series is not reported in the domestic and overseas literature.…”
Section: Introductionmentioning
confidence: 99%